The correlation between plasma reactive oxygen species and hearing threshold levels in presbycusis patients - Purnami, Nyilo; Nuraini, Anita; Surarso, Bakti (Oto Rhino Laryngologica Indonesiana, 2019)
Background: Presbycusis is a hearing loss due to the degeneration process in elderly people of 65 years old and beyond, characterized by a decrease in hearing sensitivity in both ears. Reactive oxygen species (ROS) are assumed to have an important role in the pathogenesis of presbycusis. Purpose: To find out the correlation between ROS levels in plasma and hearing threshold levels in presbycusis patients. Method: The design was cross sectional and conducted at the Outpatient Clinic of Neurotology Division, Geriatric Clinic, Clinical Pathology Installation, and Central Installation of Biomaterials Network Bank of Dr. Soetomo Hospital. Samples were taken by consecutive sampling for audiometric examination and measurement of ROS levels in plasma. Results: Fifty samples were collected, ROS levels in plasma were found with mean (SD) of 2.46 ng/ml (0.84). The mean hearing threshold level was 47.70 dB (12.42). The Pearson statistical test revealed a significant correlation between ROS levels in plasma and hearing threshold levels, with p=0.003 (p<0.05), and the correlation coefficient (r) 0.41. Conclusion: There was a correlation between ROS in plasma and hearing threshold levels in presbycusis patients, with a significant moderate-positive correlation pattern. It indicated that the higher the ROS levels in plasma, the higher the hearing threshold levels in presbycusis patients. Latar belakang: Presbikusis adalah gangguan pendengaran akibat proses degenerasi yang dijumpai pada usia 65 tahun atau lebih, ditandai oleh penurunan kepekaan pendengaran pada kedua telinga. Reactive oxygen species (ROS) diduga mempunyai peran penting pada patogenesis  presbikusis. Tujuan: Untuk mengetahui hubungan antara kadar ROS dalam plasma dengan nilai ambang dengar pada penderita presbikusis. Metode: Penelitian ini adalah cross sectional, dilakukan di Unit Rawat Jalan (URJ) THT-KL Divisi Neurotologi, URJ Geriatri, Instalasi Patologi Klinik, dan Instalasi Pusat Biomaterial Bank Jaringan RSUD Dr. Soetomo. Sampel diambil secara consecutive sampling. Diperoleh 50 sampel untuk dilakukan pemeriksaan audiometri dan pengukuran kadar ROS dalam plasma. Hasil: Kadar ROS dalam plasma didapatkan hasil rerata (SD) 2,46 ng/ml (0,84). Nilai ambang dengar didapatkan hasil rerata (SD) 47,70 dB (12,42). Hasil uji statistik dengan korelasi Pearson terhadap kadar ROS dalam plasma dan nilai ambang dengar didapatkan hasil koefisien korelasi (r) sebesar 0,41 dan p=0,003 (p<0,05). Kesimpulan: Terdapat hubungan antara kadar ROS dalam plasma dengan nilai ambang dengar pada penderita presbikusis dengan pola hubungan bersifat positif-sedang yang signifikan, yang berarti semakin tinggi kadar ROS dalam plasma, semakin tinggi nilai ambang dengar.